SAP planning : best practices in implementation - Anderson, George W. (Software architect) (Sams, 2003)
Everything a company needs to know to plan, organize, and perform an SAP implementation in one book! This is the only book available that shows the reader how to actually plan an SAP Data Center, install mySAP components, and set up the tools and processes necessary to monitor and manage a productive SAP system. It covers how to perform a Total Cost of Ownership analysis to help refine your SAP Solution Vision, and then how to leverage SAPÂ¿s technology partners to work through the SAP system landscape sizing process. Staffing the project, from the SAP Steering Committee all the way down to the primary SAP basis and computer operations teams, is covered as well. It also covers building high availability and disaster recoverability into your solutions, addressing critical training required by the SAP support team as well as end users, and how to use SAP-provided and a host of other 3rd party tools to manage your mySAP landscape. Finally, this is the only book that covers in detail how to address both functional and stress testing of your solution prior to going live. Throughout the book, knowledge and processes are provided that will help you hit the ground running and help you save money. The book is written by an SAP Technical Certified Consultant with seven years of experience in SAP design and implementation who offers tried and proven approaches, scripts, and tools similar to those used by new and existing SAP customer sites. The accompanying CD of documents, presentations, scripts, checklists, and various tools valued at $50,000 saves time and makes the reader productive fast. Coverage includes notated screen shots of real productive systems; custom checklists, how-to procedures, organization charts that can be leveraged immediately for staffing teams; PowerPoint presentations that can be used by management to sell, present, and provide status updates on their mySAP projects internally; tools, utilities, and XLS spreadsheets used to design, size, and understand SAP system architectures; actual Microsoft Project plans and implementation schedules to get the customer and 3rd party Project Manager's started quickly; and documentation templates and approaches that may be used at once.